Kultura nowoczesna – kultura interpretacji - Januszkiewicz, Michał (Fides, Ratio et Patria. Studia Toruńskie, 2016)
The article– Culture of Interpretation is an attempt to reflect on the condition of modern culture in the context of hermeneutics and semiotics. The primacy of an interpretation is inferred mainly from the intensive development of the media, the end of the grand narrations and various turns in the humanities.